WEB APPLICATION IN ONLINE PULSA charging USING Macromedia Dreamweaver MX - Budi Prayitno (Jurnal Sistem Informasi, 2007)
Internet is now a become a most effective option in disseminating information, because the Internet has a range of very large networks. One of the information received great places on the Internet include information relating to the world of communication, especially in the field of credit sales business on-line. This information is conveyed through one of the storage media of information on the Internet Web site. Developed countries in Europe to implement cellular communication technology in recent decades, the 70s, and Indonesia has only utilize the sophistication of communication dozen years later. Cellular technology into Indonesia for the first time in 1984 with technology-based Nordic Mobile Telephone (NMT). Scientific writing is trying to explain how the development of a Web site of the Toll Filling In Online. Starting from design stage to design the Web site ready to be published on the Internet. All were created using Macromedia Dreamweaver MX software.